2018
DOI: 10.1002/epi4.12272
|View full text |Cite
|
Sign up to set email alerts
|

PLPBP mutations cause variable phenotypes of developmental and epileptic encephalopathy

Abstract: SummaryObjectiveVitamin B6–dependent epilepsies are treatable disorders caused by variants in several genes, such as ALDH7A1,PNPO, and others. Recently, biallelic variants in PLPBP, formerly known as PROSC, were identified as a novel cause of vitamin B6–dependent epilepsies. Our objective was to further delineate the phenotype of PLPBP mutation.MethodsWe identified 4 unrelated patients harboring a total of 4 variants in PLPBP, including 3 novel variants, in a cohort of 700 patients with developmental and epile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 16 publications
4
53
1
Order By: Relevance
“…Here, we describe two additional patients with PLPBP ‐associated vitamin B6‐dependent epilepsy caused by homozygous variants in PLPBP , including a novel missense variant, c.121C>T, p.(Arg41Trp) and a splice‐site variant c.207+1G>A, which was previously identified in compound heterozygous state with another splice‐site variant . Pathogenicity of p.(Arg41Trp) is supported by the previous identification of the substitution of arginine 41 by glutamine in five patients with relatively mild clinical severity of vitamin B6‐dependent epilepsy due to PLPBP variants (four homozygous, one compound heterozygous) . Overall, 13 missense and 7 splice‐site and null (nonsense and frameshift) variants in PLPBP have been identified .…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…Here, we describe two additional patients with PLPBP ‐associated vitamin B6‐dependent epilepsy caused by homozygous variants in PLPBP , including a novel missense variant, c.121C>T, p.(Arg41Trp) and a splice‐site variant c.207+1G>A, which was previously identified in compound heterozygous state with another splice‐site variant . Pathogenicity of p.(Arg41Trp) is supported by the previous identification of the substitution of arginine 41 by glutamine in five patients with relatively mild clinical severity of vitamin B6‐dependent epilepsy due to PLPBP variants (four homozygous, one compound heterozygous) . Overall, 13 missense and 7 splice‐site and null (nonsense and frameshift) variants in PLPBP have been identified .…”
Section: Discussionsupporting
confidence: 61%
“…In contrast, the patients reported by Plecko et al were all treated with PN and had decent seizure control in at least three out of four cases . Three of four patients reported by Shiraku et al were treated with PN and in the latest study only one of three patients who switched from PN to PLP had improved seizure control . While these clinical data do not offer indication for superior effectiveness of either PN or PLP, studies in plpbp −/− zebrafish larvae showed a more remarkable effect of PN on the epileptic phenotype and survival with a clear dose‐dependency .…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations